RELATIONSHIP BETWEEN GREEN SUPPLY CHAIN AND LEAN SUPPLY CHAIN OF ITS EFFECT ON SUPPLY CHAIN PERFORMANCE: ANALYSIS STUDY AT AL ITTIHAD FOOD INDUSTRIES COMPANY BABYLON - Hamid Kathim Mutaab Alshbawi; Fadheelah Hussein Oleiwi Nasir (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
The current research aims to identify the relationship between the green supply chain and lean supply chain and its impact on the performance of the processing chain/analytical study at Al Ittihad Food Industries/Babylon, the research adopted the analytical descriptive approach, with the sample being 300. A member of the staff of Al Ittihad Food Industries Company Babylon, who has knowledge and skills in their field of work, where their responses were recorded on a set of test items distributed to them in a questionnaire prepared by the researcher to identify the interest and availability of the green supply chain dimensions in the company in question and the performance indicators of a chain Fit in. The results of the statistical analysis of the data showed that there are positive indications of the supply of green processing chain dimensions in Etihad Food Industries/Babylon and that these indicators are important and have a direct impact on improving the performance of the processing chain in Etihad. Therefore, the researcher recommends that companies should move toward environmental protection through awareness of the damage caused by their operations and activities in the environment. The development of the industry should be carried out by increasing attention to the dimensions of the green processing chain, namely design, procurement, green manufacturing, rapid and efficient treatment of waste, dissemination of environmental awareness to consumers and the design of marketing mix for green products according to market requirements.